2014
DOI: 10.1080/0312407x.2014.910677
|View full text |Cite
|
Sign up to set email alerts
|

A Strengths Perspective on Caregiving at the End-of-life

Abstract: The adverse effects of caregiving provided by family members, partners, and friends for people dying at home from a life-limiting illness have been extensively documented in the palliative care research literature, yet minimal attention has been directed towards the strengths of informal carers and their subsequent growth and development. Using in-depth interviews from a purposive sample of informal carers (n = 28), this paper reports empirical evidence from a subset of data analysed for an Australian qualitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Timekeeping was an important component of the process because patients were typically advised to ingest the medication quickly so as to avoid losing consciousness before finishing the lethal dose. (Buchbinder et al 2018, p4) “So I remember us sitting down and then dividing the tasks, like, father doing the shopping, and my sister would do this, and I’d do that....” (Strang & Koop, p.110) Emotion focused Caregiving as an opportunity to show love, be rewarded with closeness; frustration, sadness, or anticipatory grieving [ 27 , 32 , 33 , 36 , 37 , 42 , 44 , 45 , 47 , 51 , 54 58 , 60 , 61 , 63 ] Overall focus on fulfilling patient’s desire to avoid prolonged suffering; where hastened death was illegal or quasi-legal, moral distress in trying to reconcile patients’ request for support with own ambivalence or discomfort. In Switzerland, carrying the burden of secrecy after death [ 16 , 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Timekeeping was an important component of the process because patients were typically advised to ingest the medication quickly so as to avoid losing consciousness before finishing the lethal dose. (Buchbinder et al 2018, p4) “So I remember us sitting down and then dividing the tasks, like, father doing the shopping, and my sister would do this, and I’d do that....” (Strang & Koop, p.110) Emotion focused Caregiving as an opportunity to show love, be rewarded with closeness; frustration, sadness, or anticipatory grieving [ 27 , 32 , 33 , 36 , 37 , 42 , 44 , 45 , 47 , 51 , 54 58 , 60 , 61 , 63 ] Overall focus on fulfilling patient’s desire to avoid prolonged suffering; where hastened death was illegal or quasi-legal, moral distress in trying to reconcile patients’ request for support with own ambivalence or discomfort. In Switzerland, carrying the burden of secrecy after death [ 16 , 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Death allows patient to escape suffering. Escalating need for care results in more clinical resources [ 26 , 36 38 , 44 , 46 , 48 , 51 , 53 57 , 60 – 63 , 65 ]. Clinicians who would not facilitate hastened death but were supportive in other ways; in retrospect, hastened death seen as right choice [ 15 , 16 , 18 , 19 , 70 ] “I mean it’s so wonderful that you can give someone yourself.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout the uncertainty of providing end‐of‐life care, carers regularly faced experiences that were beyond familiar frames of reference and they often felt helpless and trapped in their roles (Collins et al, ; Hughes, ; Lewis, ; Stajduhar et al, ). Alongside feeling trapped, some carers looked towards the impending death of care recipients as a necessary event that must occur in order for them to once again have their own life (Lewis, ).…”
Section: Resultsmentioning
confidence: 99%
“…A consideration of the personal implications of providing end‐of‐life care most clearly demonstrates how PCP can provide a coherent framework for understanding the challenges carers face. In particular, the reviewed literature suggests that carers encounter experiences that are beyond anything familiar as care recipients approach end‐of‐life (Hughes, ; Lewis, ). Due to the unknown future they face, literature has suggested that carers develop new identities (e.g., the “carer persona”—Broady, ) to manage the unexpected and to protect themselves from any fear of what is to come (Carlander et al, ).…”
Section: Discussionmentioning
confidence: 99%